2022
DOI: 10.1186/s12904-022-01080-6
|View full text |Cite
|
Sign up to set email alerts
|

The end of life experiences of people living with socio-economic deprivation in the developed world: an integrative review

Abstract: Background Those experiencing socioeconomic deprivation have poorer quality of health throughout their life course which can result in poorer quality of death – with decreased access to palliative care services, greater use of acute care, and reduced access to preferred place of care compared with patients from less deprived populations. Aim To summarise the current global evidence from developed countries on end-of-life experience for those living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Further, not only are conventional notions of the ‘good death’ deeply embedded in privilege 20 , but lifelong health inequities are intensified at the EOL – Corpora’s work, underpinned by intersectionality, shows how generational and structural racial disparities and disadvantage compound, leading to inequitable dying experiences 21▪▪ . People with socioeconomic deprivation are more likely to have: a higher symptom burden; greater difficulty navigating complex healthcare systems and higher use of health care when they do have access; a preference for and greater use of intensive treatment at the EOL; limited formal and informal social support; and are more likely to experience financial distress at EOL 22▪▪ . Findings from an ethnographic study in the ICU highlighted how those who are socially disadvantaged are more likely than others to conceptualise the ‘good death’ as having active treatment 23▪▪ .…”
Section: Resultsmentioning
confidence: 99%
“…Further, not only are conventional notions of the ‘good death’ deeply embedded in privilege 20 , but lifelong health inequities are intensified at the EOL – Corpora’s work, underpinned by intersectionality, shows how generational and structural racial disparities and disadvantage compound, leading to inequitable dying experiences 21▪▪ . People with socioeconomic deprivation are more likely to have: a higher symptom burden; greater difficulty navigating complex healthcare systems and higher use of health care when they do have access; a preference for and greater use of intensive treatment at the EOL; limited formal and informal social support; and are more likely to experience financial distress at EOL 22▪▪ . Findings from an ethnographic study in the ICU highlighted how those who are socially disadvantaged are more likely than others to conceptualise the ‘good death’ as having active treatment 23▪▪ .…”
Section: Resultsmentioning
confidence: 99%
“…We observed that higher affordability, measured at the neighborhood level with indicators of poverty rates and educational attainment at the time of ovarian cancer diagnosis, was associated with better quality EOL care outcomes. Patients in low-income neighborhoods experience higher levels of socioeconomic deprivation, which may directly contribute to the observed affordability pattern, through higher financial distress, higher physical symptom burden, poorer health and function, failure of existing health care resources and services to meet low-income patients’ complex needs leading to repeated utilizations, and an inherent preference for more intensive EOL care ( 30 ). Conversely, patients with ovarian cancer in affluent neighborhoods may benefit from access to higher health care quality, including better pain and symptom management ( 31 ), corresponding to less comorbidity burden and outcome severity, thus reducing the need for health care utilization during EOL.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with complex ovarian cancer disease and symptom management needs, NHB patients may require ER or inpatient hospitalizations for treatment ( 16, 36, 37 ). Moreover, due to the inability to afford out-of-pocket or informal costs not covered by Medicare, including travel and time of nonpaid caregivers, high-quality EOL care such as hospice use may be beyond the reach of many NHB patients ( 30, 38, 39 ). NHB patients may actively pursue Medicare-covered rehabilitation services to avoid out-of-pocket hospice costs ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to their more affluent neighbours, persons who experience socioeconomic hardship spend a greater proportion of their shorter lives in poor health and carry a heavier load of chronic diseases, multi-morbidity, and symptom burden. Socioeconomic disadvantage is a risk factor on its own for greater mortality in populations with and without cancer and is linked to higher healthcare utilization and expenditures in the last year of life [9].…”
Section: Discussionmentioning
confidence: 99%